Fuzzy Logic Based Power-Efficient Real-Time Multi-Core System - Ahmed, Jameel; Siyal, Mohammed Yakoob; Najam, Shaheryar; Najam, Zohaib; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book focuses on identifying the performance challenges involved in computer architectures, optimal configuration settings and analysing their impact on the performance of multi-core architectures. Proposing a power and throughput-aware fuzzy-logic-based reconfiguration for Multi-Processor Systems on Chip (MPSoCs) in both simulation and real-time environments, it is divided into two major parts. The first part deals with the simulation-based power and throughput-aware fuzzy logic reconfiguration for multi-core architectures, presenting the results of a detailed analysis on the factors impacting the power consumption and performance of MPSoCs. In turn, the second part highlights the real-time implementation of fuzzy-logic-based power-efficient reconfigurable multi-core architectures for Intel and Leone3 processors. .
Multiprocessors and Cache Memory -- Energy Delay Product and Throughput -- Challenges and Issues in Modern Computer Architectures -- Real-Time Power And Performance Aware System -- Fuzzy Logic Theory. .
Keywords: Computational intelligence; Microprocessors; Computer architecture; Electronic circuits; Computational Intelligence; Processor Architectures; Electronic Circuits and Systems